SUKUK RATING AND FINANCIAL RATIO IN ISLAMIC BANKS - Kurnia Agustina; Heni Noviarita; Erike Anggraini; Surono surono (Tasharruf: Journal Economics and Business of Islam, 2021)
The sukuk rating in capital market world is important because it will be considered by investors in determining investment decisions, on the other hand, that the rating will provide relevant information regarding the companies that issue sukuk, which will be in accordance with the main purpose of the sukuk rating, namely reducing the information asymmetry of issuers and investors purpose of this study is to discuss the effect of profitability ratios, liquidity ratios, leverage and productivity ratios on sukuk ratings in Islamic banking institutions issuing sukuk. By using purposive sampling from 14 Islamic banking institutions, 6 Islamic bank institutions were obtained as research samples in the 2015-2019 period, which were analyzed using multiple linear regression showing that only the productivity variable had a significant and positive influence on the rating of sukuk in Islamic banking institutions, although, with a positive coefficient, profitability does not have a significant effect on the sukuk rating, while the liquidity and leverage variables do not have a significant effect and form a negative relationship pattern on the sukuk rating in Indonesian Islamic banking institutions that issue sukuk.